Transport documents in carriage of goods by sea international law and practice - Pejovic, Caslav (Maritime and transport law library, 2020)
Bringing a fresh, comparative approach to transport documents used in the carriage of goods by sea, this book covers bills of lading, sea waybills, ship's delivery orders, multimodal transport documents, and electronic transport documents. The book covers historic developments, current conventions, and thoughts for the future on these transport documents; and delves deeply into the legal issues concerning them. It represents a comprehensive compilation of case and statute law from around the world on this subject. In addition to English law, the book covers American, French, German, and Italian laws, as well as the laws of several East Asian jurisdictions (China, Japan, South Korea). Primarily, the book will be of use to maritime law scholars and students, and lawyers who deal with shipping. It may also be of interest to international traders, banks, and ship masters and officers.